Nursing care in the postoperative period of cardiac surgery in light of Wanda Horta's Theory (Research, Society and Development, 2024)
Introduction: Wanda Horta's theory proposes, through attention to basic human needs, a comprehensive, holistic, and individualized approach to care, a fundamental factor in the intensive care of post-cardiac surgery patients. Objective: To identify nursing care in the postoperative period of cardiac surgery, in an Intensive Care Unit (ICU), in light of Wanda Horta's theory. Methodology: Qualitative study involving nurses providing care to post-cardiac surgery patients in an ICU in Southern Brazil. Semi-structured online interviews were conducted, and thematic analysis was performed to data treatment. Results: Nine nurses participated, aged between 34 and 40 years, mostly women, with experience in ICU and care for these patients. Three categories emerged: Complexity of Nursing Care; Psychobiological and Psychosocial Needs; Care Gaps in the Face of Psycho-spiritual Needs. Final considerations: Nurses demonstrated knowledge of post-cardiac surgery protocols and acknowledged the complexity of care. They recognized that psychobiological and psychosocial needs take precedence over psycho-spiritual needs. It is suggested to pay more attention to establishing this dimension within ICUs.